The bidirectional relationship between depression and diabetes - Chilimoniuk, Zuzanna; Dobosz, Maciej; Chałupnik, Aleksandra; Borkowska, Aleksandra; Mizerski, Grzegorz (Journal of Education, Health and Sport, 2022)
Introduction and objective: In recent years, depression and diabetes have become more and more serious medical issues. The number of patients suffering from one or both of these disorders increases year by year, which significantly worsens their quality of life. The aim of the study is to present the current state of knowledge on the basic mechanisms and risk factors influencing the development of depression in patients with diabetes, as well as the bidirectional relationship between these illnesses. The study was based on a literature review and an analysis of publications available on PubMed and Google Scholar platforms. The search has been conducted with the use of a combination of keywords like: “diabetes type 1”, “diabetes type 2”, “depression”, “mental health”. An abbreviated description of the state of knowledge: Every third patient with diabetes shows depressive symptoms. These psychological disorders are more common in people with type 1 diabetes. The most vulnerable group of patients are single women with low socioeconomic status and comorbidities. Numerous biochemical and psychosocial changes in the life of diabetic patients, significantly increase the risk of developing depression. The latest scientific reports also draw attention to the two-way relationship between diabetes and depression. The inclusion of cognitive-behavioral therapy brings positive results in managing diabetes with comorbid depression. Summary: The available scientific data clearly shows the existence of psychological and biological links between these two disease entities. Appropriate diagnosis and treatment of depressive disorders can improve the course of diabetes.